Amenity benefits and the optimal allocation of land. - Lopez, Rigoberto A.; Shah, Farhed A.; Altobello, Marilyn A. (Land Economics, 1994)
A study confirms that agricultural land offers important amenity benefits not accounted for in existing allocations of land for agriculture. Agricultural and demographic data on 216 counties in the northeastern U.S. were analyzed in a supply-demand model; willingness-to-pay information from prior studies was used to derive an amenity benefit function. Regression results suggest that, in highly urbanized areas, land is underallocated to agriculture given existing regulations. Results show that a rise in population reduces the amount of agricultural land. Meanwhile, community willingness-to-pay to preserve agricultural land increases at a declining rate with respect to land. The findings suggest that subsidizing agricultural activities can achieve a socially optimal allocation of land.